Economic Constraction Vs Mental Beggars During the Covid 19 Pandemic 2021 - Soenjoto, Wening Purbatin Palupi; Soleha, Arin Ramadhiani; Amin, Eka Mulia Nurul Al (The Sunan Ampel Review of Political and Social Sciences, 2023)
The covid pandemic period that occurred until the end of 2021 changed many aspects of human life. There was a global psychological shock and had to change habits suddenly into polemics. Changing habits is not an easy thing, it requires great effort to want to follow the rules of new normal life. The 19th pandemic period became a rationalization of the economic situation of a group of people who felt they had the right to receive social assistance from the government. This was because a preconceived mental formation was a mental formation formed by the soul asking for material deficiency. The government provides social assistance funds in dealing with the economy in Indonesia with the intention of providing assistance to help people affected by the pandemic. Many companies are laying off workers on a large scale which has led to increased unemployment. The state of global conflict in all aspects, especially the economic aspect, which causes economic contraction, but with social assistance, a beggar mentality is even triggered. The assistance funds provided are not to open a business as a substitute for a profession because they are unemployed due to being affected by the pandemic by becoming entrepreneurs. hope that every month they will receive aid funds from the government. There is also a mistargeting of the distribution of social assistance funds and many receive it even though it is not their right to receive social assistance funds.